It isn't working: Time for more radical policies - Éric Tymoigne; L. Randall Wray (Levy Economics Institute of Bard College, 2009)
The Obama administration has implemented several policies to jump-start the American economy - efforts that have largely focused on preserving the financial interests of major banks. The authors of this new policy brief believe that maintaining the status quo is not the solution, since it overlooks the debt problems of households and nonfinancial businesses - and re-creating the financial conditions that led to disaster will simply set the stage for a recurrence of the Great Depression or a Japanese-style lost decade. They recommend a more radical policy agenda, such as federal spending programs that directly provide jobs and sustain employment, thereby helping to restore the creditworthiness of borrowers, the profitability of firms, and the fiscal position of state and federal budgets.
Keywords: 330